2013
DOI: 10.1124/dmd.113.053082
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Oxidase 1 (AOX1) in Human Liver Cytosols: Quantitative Characterization of AOX1 Expression Level and Activity Relationship

Abstract: Aldehyde oxidase 1 (AOX1) is a cytosolic enzyme highly expressed in liver and plays a key role in metabolizing drugs containing aromatic azaheterocyclic substituents. Rapid metabolism catalyzed by AOX1 can cause a drug to exhibit high clearance, low exposure, and hence decreased efficacy or even increased toxicity (if AOX1 generated metabolites are toxic). There is a need to develop the correlation between AOX1 expression levels and AOX1-substrate clearance. A fast, sensitive, and robust liquid chromatography-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 32 publications
1
40
0
1
Order By: Relevance
“…Interestingly, evaluation of the medical history data of the donors revealed that three of the five low-activity donors had histories of extensive alcohol abuse up until time of death. This acute effect of alcohol abuse was also recently reported by scientists at Pfizer (Fu et al, 2013). The exact mechanism of this alcohol effect on AO activity was (Fu et al, 2013).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Interestingly, evaluation of the medical history data of the donors revealed that three of the five low-activity donors had histories of extensive alcohol abuse up until time of death. This acute effect of alcohol abuse was also recently reported by scientists at Pfizer (Fu et al, 2013). The exact mechanism of this alcohol effect on AO activity was (Fu et al, 2013).…”
Section: Discussionmentioning
confidence: 76%
“…This acute effect of alcohol abuse was also recently reported by scientists at Pfizer (Fu et al, 2013). The exact mechanism of this alcohol effect on AO activity was (Fu et al, 2013). Thus, the presence of AO protein apparently does not correlate with activity, which complicates the assessment of variability factors.…”
Section: Discussionmentioning
confidence: 93%
“…UGT2B4 is a member of the UDP glucuronosyltransferase family, which consists of phase II drug metabolism enzymes (10,33). AOX1 is an oxidase that plays a key role in the metabolism of xenobiotics and drugs containing aromatic azaheterocyclic substituents (12). Finally, CYP2E1, a member of the cytochrome P450, is a phase I drug-metabolizing enzyme (33), and differences in epigenetic regulation of CYP2E1 between hPSC-HEP and primary hepatocytes have been determined (36), which may account for the impaired activity of this enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the levels between the two methods vary greatly from 0.74-2.3 pmol/mg cytosolic protein (Fu et al, 2013) to 21-40 pmol/mg cytosolic protein . The discrepancy, whether due to enzyme source, preparation, or differences in the quantification method, warrants a number of further assessments to reach a consensus and provide a best practice for quantifying AO.…”
Section: In Vitro Sources Of Ao Activity and Their Utility In Assessimentioning
confidence: 99%